Association between Quantitative Classification of Renal Surface Nodularity and Early Renal Injury in Patients with Arterial Hypertension. (4th March 2022) - Zhou, Jun; Ding, Jiule; Chen, Jie; Wu, Qiong; Xiang, Dehui; Xing, Wei
Abstract : Background . This study sought to explore the association between quantitative classification of renal surface nodularity (qRSN) based on computed tomography (CT) imaging and early renal injury (ERI) in patients with arterial hypertension. Methods . A total of 143 patients with a history of hypertension were retrospectively enrolled; clinical information (age, sex, hypertension grade, and hypertension course), laboratory tests, and qRSN were collected or assessed. The subjects were divided into an ERI group ( n  = 60) or a control group (CP, n  = 83) according to ERI diagnosis based on the following criteria: cystatin C > 1.02 mg/L. Univariate analysis and multiple logistic regression were used to assess the association between ERI and qRSN. A receiver operating characteristic curve (ROC) was performed to compare multiple logistic regression models with or without qRSN for differentiating the ERI group from the control group. Results . In univariate analysis, hypertension grade, hypertension course, triglycerides (TG), and qRSN were related to ERI in patients with arterial hypertension (all P < 0.1 ), with strong interrater agreement of qRSN. Multiple logistic regression analysis showed an area under the ROC curve of 0.697 in the model without qRSN and 0.790 in the model with qRSN, which was significantly different ( Z  = 2.314, P = 0.021 ). Conclusion. CT imaging-based qRSN was associated with ERI in patients with arterial hypertension and may be an imaging biomarker of early renal injury.